The branchiostegal lung of Uca vocans (Decapoda: Ocypodidae): Unreported complexity revealed by corrosion casting and MicroCT techniques. Issue 6 (November 2015) - Paoli, Francesco; Wirkner, Christian S.; Cannicci, Stefano
Abstract: The study of adaptation to terrestrial life in crabs poses several physiological questions. One of the major challenges the crabs have to face is respiration of air: most of the time, gills are unsuitable to perform oxygen exchange out of the water. Fiddler crabs, like other representatives of the Ocypodidae, have developed an additional mechanism of respiration by improving the circulation that lines the branchiostegal chamber, thus developing a branchiostegal lung. In the present study we describe the hitherto unreported complex morphology of the branchiostegal lung of the fiddler crab Uca vocans by means of corrosion casting techniques and 3D reconstruction. This complexity leads us to reconsider the degree of terrestriality of U . vocans and its evolutionary pathway towards land. Graphical abstract: Highlights: The branchiostegal lung of Uca vocans was 3D reconstructed. A hitherto unknown complexity of the lung was reported. A comparison with the branchiostegal lung of Ocypode cordimanus was carried out.